THE ROLE OF THE RUSSIAN LANGUAGE IN SOCIETY - Nargiza Ziraddinovna Mammadova (Web of Journals Publishing, 2024)
This article delves into the multifaceted role of the Russian language in contemporary society, exploring its historical significance, cultural implications, and contemporary relevance. Through a comprehensive literature analysis, this study aims to shed light on the various dimensions of the Russian language, examining its impact on identity, communication, and international relations. By employing a systematic approach, this research provides valuable insights into the language's dynamic role in shaping societal dynamics.
Keywords: Russian language, linguistic identity, cultural heritage, communication, international relations.